The utility for identification of best available evidence of a register of controlled studies that evaluate interventions to prevent alcohol-impaired driving. (1st March 2011) - Goss, C; Roberts, I; DiGuiseppi, C
Abstract : Objective: To evaluate whether a register of controlled studies can facilitate the conduct of systematic reviews. Methods: We searched 11 bibliographic databases, contacted 97 government agencies, and hand searched conference proceedings to identify randomised, quasi-randomised, controlled before-after and interrupted time series studies of interventions to prevent alcohol-impaired driving. We tested the register's utility against three published reviews. We first searched the register for the 22 review citations that had eligible study designs, matching exact citations or related/follow-up studies. We then screened 764 unmatched register citations for studies not cited in the reviews, examining full-text reports to determine eligibility based on the reviews' inclusion criteria. We assessed the register's comprehensiveness (proportion of review citations found in the register), added value (additional eligible studies identified), and utility for updates (identification of eligible studies completed since the reviews were conducted). Results: The register included 16/22 (73%) review citations: 100% for designated-driver programs, 73% for school-based programs and 60% for mass media campaigns. It included 15/18 (83%) journal articles but only 1/4 (25%) government/technical reports. The register yielded three eligible studies of school-based programs not previously cited, increasing the total identified, relevant studies by 14%, and four studies eligible for review updates. Quality assessments are ongoing. Conclusion: A trial register can enhance systematic reviews of interventions to prevent alcohol-impaired driving by increasing identification of available evidence. However, additional effort is needed to identify government reports and other 'gray literature.' The register is regularly updated and accessible through the Cochrane Injury Group's specialised register.